Densification of the interlayer spacing governs the nanomechanical properties of calcium-silicate-hydrate - Geng, Guoqing; Myers, Rupert J.; Qomi, Mohammad Javad Abdolhosseini; Monteiro, Paulo J. M. (Scientific reports, 2017)
Calciuam-silicate-hydrate (C-S-H) is the principal binding phase in modern concrete. Molecular simulations imply that its nanoscale stiffness is ‘defect-driven’, i.e., dominated by crystallographic defects such as bridging site vacancies in its silicate chains. However, experimental validation of this result is difficult due to the hierarchically porous nature of C-S-H down to nanometers. Here, we integrate high pressure X-ray diffraction and atomistic simulations to correlate the anisotropic deformation of nanocrystalline C-S-H to its atomic-scale structure, which is changed by varying the Ca-to-Si molar ratio. Contrary to the ‘defect-driven’ hypothesis, we clearly observe stiffening of C-S-H with increasing Ca/Si in the range 0.8 ≤ Ca/Si ≤ 1.3, despite increasing numbers of vacancies in its silicate chains. The deformation of these chains along the b -axis occurs mainly through tilting of the Si-O-Si dihedral angle rather than shortening of the Si-O bond, and consequently there is no correlation between the incompressibilities of the a- and b- axes and the Ca/Si. On the contrary, the intrinsic stiffness of C-S-H solid is inversely correlated with the thickness of its interlayer space. This work provides direct experimental evidence to conduct more realistic modelling of C-S-H-based cementitious material.